Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jpcc.1c01387
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control of Tantalum Carbide Nanoparticles through Dopant Additions

Abstract: The control of powder morphology in metals and ceramics is of critical importance in applications such as catalysis and chemical sensing whereby specific crystal facets better facilitate chemical reactions. In response to this challenge, we present a combined experimental and computational approach that examines the principles behind dopant-induced crystallographic faceting in nanoparticles. We base our study on nanoparticles of tantalum carbide doped with nickel, iron, cobalt, niobium, and titanium and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The presence of needle-like structures and incomplete elongated crystals shows the presence of α-MoO 3 , which agrees with the XRD and Raman results. Thus, from SEM, it is seen that powder morphologies can be controlled by varying the phases in this material. The darker rectangular structures from samples AP10 and AP15 were analyzed by EDS and are depicted in Figure .…”
Section: Resultsmentioning
confidence: 85%
“…The presence of needle-like structures and incomplete elongated crystals shows the presence of α-MoO 3 , which agrees with the XRD and Raman results. Thus, from SEM, it is seen that powder morphologies can be controlled by varying the phases in this material. The darker rectangular structures from samples AP10 and AP15 were analyzed by EDS and are depicted in Figure .…”
Section: Resultsmentioning
confidence: 85%
“…It is observed that the temperature is enhanced with enhancing for other values of the parameters under consideration. Inversely, it is noticed from Figs 13. and 14 that Φ !…”
mentioning
confidence: 89%
“…It has been seen that hybrid nanoparticles have been utilized widely in order to overcome the shortcomings of single-component nanoparticles, to boost functions and to achieve specific effects for single nanoparticle. The tantalum carbide nanoparticle was, therefore, researched by Ren et al [13] along with cobalt and other metal dopants in 2021 where it was concluded that they provide a promising potential in the modification of the mechanical and catalytic characteristics of ceramic materials. Zhang et al [14] conducted an in-vitro study to observe the oxidative stress and cytotoxicity of tantalum on macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16–19 ] In particular, transition metal carbides such as tantalum carbide (TaC) and hafnium carbide (HfC) have gained significant interest because they possess the highest melting temperatures, above 4000 K, among transition metal carbides. [ 20 ] TaC and HfC crystallize in the cubic rock‐salt (Fnormalmtrue3¯normalm$F \text{m} \bar{3} \text{m}$) structure and exhibit mixed covalent, ionic, and metallic bonding, [ 21 ] which gives rise to high thermal conductivity (≈55.8 W m −1 ⋅ K), [ 22 ] significant flexural strength (≈500 MPa), [ 23,24 ] and relatively high hardness (≈15 GPa). [ 25,26 ] These carbides can also form a passive oxide surface layer that provides some oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%